2020
DOI: 10.2147/dddt.s274307
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Switching from Tenofovir Disoproxil Fumarate (TDF) to Tenofovir Alafenamide (TAF) on Liver Enzymes, Glucose, and Lipid Profile</p>

Abstract: Objective We aimed to investigate the effect of switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF) on the hepatic safety and metabolic profile. Methods Consecutive HIV patients, enrolled in the Surveillance Cohort Long-term Toxicity Antiretrovirals/Antivirals (SCOLTA) project, switching from TDF to TAF were included. Changes from baseline (T0) to 6-month follow-up (T1) were evaluated using paired t -test and sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 23 publications
5
32
0
1
Order By: Relevance
“…The magnitude of lipid increases observed in this study (CHOL: + 7.9%, LDL: + 11.1%, HDL: + 7.1%, TG: + 23.8%) was consistent with the results of a smaller observational study of 238 PLWH switching from TDF to TAF, which reported statistically significant relative increases in CHOL, LDL and HDL of a similar magnitude to those reported here [ 19 22 ]. However, other observational studies reported larger statistically significantly increases in lipids for up to 6 months after switch [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The magnitude of lipid increases observed in this study (CHOL: + 7.9%, LDL: + 11.1%, HDL: + 7.1%, TG: + 23.8%) was consistent with the results of a smaller observational study of 238 PLWH switching from TDF to TAF, which reported statistically significant relative increases in CHOL, LDL and HDL of a similar magnitude to those reported here [ 19 22 ]. However, other observational studies reported larger statistically significantly increases in lipids for up to 6 months after switch [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…ASCVD atherosclerotic cardiovascular disease, n number; PLWH people living with HIV, TAF tenofovir alafenamide, TDF tenofovir disoproxil fumarate. a Pre-switch: ASCVD calculated ≤ 6 months before the last lipid panel on TDF; statin prescription at or after the last lipid panel on TDF; Post-switch: ASCVD calculated ≤6 months before the first lipid panel on TAF; statin prescription at or after the first lipid panel on TAF reported here [19][20][21][22]. However, other observational studies reported larger statistically significantly increases in lipids for up to 6 months after switch [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only 54% of patients in our cohort were switched from regimens containing cobicistat or ritonavir, and 25% were switched from regimens containing TDF. These results are somewhat unusual given the known lipid-lowering effects of TDF compared with TAF [ 29 31 ] and suggest that B/F/TAF may be more “lipid-neutral” compared with other ARV regimens. Given the increased risk of vascular disease and metabolic complications among older PLWH, [ 4 ] these data are critical and highlight B/F/TAF as a potentially “lipid-friendly” ARV option for this population.…”
Section: Discussionmentioning
confidence: 97%